Comparison of taphonomic progression due to the necrophagic activity of geographically disparate scavenging guilds. Issue 1 (2nd January 2017) - O'Brien, R. Christopher; Appleton, Avery J.; Forbes, Shari L.
ABSTRACT: Taphonomy, the study of the progression of living things from death to decay or fossilization, is crucial for understanding and determining the post mortem interval. One of the many factors that influence the taphonomic development of a set of remains is scavenger activity. Animals that feed on a carcass can greatly influence the interpretation of the circumstances which have led to the deposition of the body, thus it is important to be able to characterise how necrophagy impacts decomposition. Because the species of scavengers vary greatly depending on the region, information must be gathered in different areas that can provide generalizations for diverse geographic locations. This study seeks to characterise and compare the decomposition rates of remains in Western Australia and in Ontario, Canada. Domestic pig ( Sus scrofa ) carcasses were placed in four locations near Perth, Western Australia and in two locations in Ontario, Canada. These were observed using trail cameras to document scavenging activity and the progression of decay. The results showed that even when climatic variable are taken into account, the effects of scavenging on decompositional rates are significant. Information from this research provides insight into the influence of distinct scavenging guilds on decomposition and how understanding the necrophagy of local fauna may contribute to the interpretation of a death scene.